Prevalence of general and abdominal obesity in Portugal: comprehensive results from the National Food, nutrition and physical activity survey 2015-2016 - Oliveira, Andreia (2018)
BACKGROUND: This study includes, for the first time, estimates of general and abdominal obesity prevalence for all ages of the Portuguese population, using common standardized methodologies. Results are compared by sex, age groups, educational level and geographical regions. METHODS: Participants were a representative sample of the Portuguese population aged between 3 months and 84 years of age (n = 6553), enrolled in the National Food, Nutrition and Physical Activity Survey, 2015-2016. Objective anthropometric measurements included length/height, weight and body circumferences, performed according to standard procedures. Body mass index (BMI) was classified according to the World Health Organization (WHO) growth charts for children and adolescents, and WHO criteria for adults. Abdominal obesity was defined in adults as waist-hip ratio ≥ 0.85 in women or ≥ 0.90 in men. Prevalence estimates and 95% confidence intervals (95%CI) were weighted according to a complex sampling design, considering stratification by seven geographical regions and cluster effect for the selected Primary Health Care Unit. RESULTS: The national prevalence of obesity is 22.3% (95%CI: 20.5-24.0), significantly higher in women. Obesity prevalence is much higher in the elderly (39.2%, 95%CI. 34.2-44.2), while children and adolescents have the lowest prevalence around 8-9%. In a regression model, three knot points denoting an inflection of obesity prevalence across the life span were observed around 5, 15 and 75 years. The prevalence of pre-obesity at national level is 34.8% (95%CI: 32.9-36.7), higher in men, and almost 18% of children and 24% of adolescents have pre-obesity. The sex- and age-standardized prevalence of obesity ranged from 38.3% (95%CI: 34.6-42.1) to 13.1% (95%CI: 10.3-15.9) for the less and the most educated individuals, respectively. Although some geographical region disparities, obesity prevalence did not significantly differed across regions (p = 0.094). The national prevalence of abdominal obesity in adults is 50.5% (95%CI: 47.9-53.1), particularly high in the elderly (80.2%). CONCLUSION: Almost 60% of the general Portuguese population is obese or pre-obese. Women, elderly and less educated individuals present the highest obesity prevalence. Abdominal obesity, in particular, seems to be a relevant public health problem among the elderly men.